El diario íntimo de un exiliado. Ramón Gil Navarro entre Argentina, Chile y California (1845-1856) Estudio preliminar y edición crítica - Blumentahl, Edward; Zubizarreta, Ignacio (Historamericana, 2023)
Ramón Gil Navarro's diary is probably one of the most reliable self-portraits of the life in exile of a member of the Spanish-American social elite of the mid-19th century. The intimate nature of the writing allows us to glimpse aspects of daily life, sexuality and material culture that are often obscured in the sources of the time. While it allows addressing issues such as exile policies, Romanticism in vogue or national representations from a new perspective. A member of the Spanish-American social elite in the mid-19th century, Ramón Gil Navarro led a life of exile. His diary provides intimate insights into aspects of everyday life, sexuality, and material culture that are often hidden in contemporary sources.